2021
DOI: 10.1101/2021.09.16.21263690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Considerations regarding a diagnosis of Alzheimer’s Disease before dementia: a systematic review

Abstract: Introduction: The NIA-AA research framework proposes a purely biological definition of Alzheimer's Disease (AD). This implies AD can be diagnosed based on biomarker abnormalities. While this brings opportunities, it also raises challenges. Methods: We conducted a systematic review by searching PubMed for publications on conveying AD biomarker results to individuals without dementia. Content was analyzed inductively. Results: We included 25 publications. From these we extracted 26 considerations, which we g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(427 reference statements)
0
2
0
Order By: Relevance
“…24,25 To address these issues, we recently conducted a systematic review of theoretical data, and identified 26 diverse and contradictory considerations related to a clinical, personal, and societal context. 26 A next step is to examine how these, and perhaps other, aspects are perceived by stakeholders, including the general public, patients, families, and health-care professionals. In this study, we therefore aimed to provide an overview of empirical data on expected and experienced implications of sharing AD biomarker results with individuals who do not have dementia (yet).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 To address these issues, we recently conducted a systematic review of theoretical data, and identified 26 diverse and contradictory considerations related to a clinical, personal, and societal context. 26 A next step is to examine how these, and perhaps other, aspects are perceived by stakeholders, including the general public, patients, families, and health-care professionals. In this study, we therefore aimed to provide an overview of empirical data on expected and experienced implications of sharing AD biomarker results with individuals who do not have dementia (yet).…”
Section: Introductionmentioning
confidence: 99%
“…Despite many decades of research, neurodegenerative diseases remain a major threat to human health and are a substantial cause of mortality. Alzheimer's disease (AD) is the most common type of dementia, and currently no therapeutics can halt or significantly slow its fatal progression [33]. Furthermore, short of an autopsy, there is no definitive way to diagnose AD and it is in general impossible to predict who will develop the disease.…”
Section: Introductionmentioning
confidence: 99%